Déterminismes De La Dynamique De La Forêt Des Marais Tanoé-Ehy (Sud-Est, Côte d’Ivoire)v - Emmanuel Joël, Abrou N’Gouan; Bruno, Kpangui Kouassi; Aimé, Vroh Bi Tra; Yves, Adou Yao Constant (European Scientific Journal, ESJ, 2017)
Objective: The Tanoé-Ehy Forest (FMTE) has been identified as a top priority site for primate conservation in West Africa. Pending the completion of the measures of its final classification in protected area, anthropic pressures are constantly nibbling the types of habitat that the FMTE contains. The objective of the present study was to analyze the spatial and temporal evolution of this forest from 1986 to 2016. The study consisted in mapping and following through Landsat satellite images from 1986, 2000, and 2016 the dynamics of the land use that constitute the FMTE. To better understand the underpinnings of this evolution, based on anthropogenic threats, surveys were carried out in the five villages closest to the forest. Treatments show a 10% degradation of swamp forest area to degraded forests in 30 years. The habitats temporarily flooded forests remained intact during this 30 years period, reflecting efforts to maintain the integrity of the FMTE. Surveys have shown that the types of pressure and their intensity vary from peripheral villages. Overall, this involves wood harvesting and hunting. In view of the importance of the FMTE in terms of a particular ecosystem and the conservation of biodiversity, it is desirable and urgent that, in addition to awareness-raising campaigns for local populations, the process of its final ranking be accelerated to end its degradation.